Neisseria gonorrhoeae betalactamase producers resistantto azithromycin in Manaus, Amazonas, Brazil - Ferreira, William A.; Ferreira, Cristina M.; Schettini, Antonio P.M.; Sardinha, José Carlos G.; Benzaken, Adele S.; Garcia, Mirna A.; Garcia, Enrique G.; Oliveira, Luiz A. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:it’s essential to monitor the susceptibility of N. gonorrhoeaeto antibiotics as a means of assuring the efficiency of the therapeuticprotocols. This study was designed to test the behavior of strains of N. gonorrhoeaebetalactamase producer against threes of the most frequently pre-scripts antibiotic for the management of gonoccocal urethral and cervical discharge in our region. Objective:to determine, using ephysolometricmethod, the in vitro susceptibility of N. gonorrhoeaebetalactamase producers strains against azithromycin, ceftriaxone and ciprofloxacin. Method:the ephisolometric test (e-test) was used to determine the susceptibility of 41 strains of N. gonorrhoeae betalactamase producer against azithromycin,ceftriaxone and ciprofloxacin in samples of urethral and cervical discharge colleted from patients seen at the Sexual Transmitted Disease Center ofFundação Alfredo da Matta (FUAM) from July to December, 2002. Results:the results showed that 21,9% (9/41) of the strains were resistant toazithromycin and 29,6% (12/41) showed reduced sensibility. Nine point seven percent (9,7% - 4/41) of the isolates showed reduced sensibilityagainst ciprofloxacin, whereas towards ceftriaxone the sensibility was 95,1% (39/41). The MIC four two of the strains tested against ceftriaxone wereabove 0,25μg/ml which is the highest value for sensibility to this antibiotic. Conclusion:this study is the first report of N. gonorrhoeaeresistant toazithromycin among the patients seen at FUAM. Also, it’s important to underline the demonstration of reduced sensibility to ciprofloxacin and MICvalues above the standard for sensibility to ceftriaxone. These results raise the possibility of therapeutic failure in the near future when these antibi-otics are used in the treatment. It is important to maintain programs of periodic evaluation of the drugs used in the syndromic treatment of urethraland cervical discharge.